Philosophical Groundwork for Multicultural Education - Erham Budi Wiranto (Prosiding University Research Colloquium, 2021)
Multicultural Education lacks a solid foundation since it appears to be a reaction to socio-political developments rather than the outcome of philosophical principles from the Philosophy of Education. Multicultural Education lacks defined concepts, methods, andorientations due to its confusing ontological, epistemological, and axiological frameworks.This article is based on a review of the literature on Political and Social Philosophy,which was then reflected in the Philosophy of Education structure. The result is aPhilosophical Foundation for Multicultural Education that is more oriented on the fieldof education while maintaining the basic notions of multiculturalism, which are foundedon political and social sciences.